S2e-Leitlinie der Deutschen Urologen: instrumentelle Therapie des benignen Prostatasyndroms - Bschleipfer, Thomas; Michel, Maurice Stephan (Der Urologe, 2016)
This report summarizes the relevant aspects of the S2e guideline of the German Urologists for the instrumental treatment of the lower urinary tract symptoms due to benign prostatic hyperplasia. Recommendations are given regarding open and transurethral procedures (TUR-P, bipolar TUR-P, TUI-P, HE-TUMT, TUNA, and the different Laser techniques). Recommendations are also given concerning intraprostatic stents and injection therapies. The influence of the different therapeutic options on bladder outlet obstruction (BOO) is described in detail.
Gesehen am 24.01.2019
Online publiziert: 1. November 2015